Answer:
second option
Step-by-step explanation:
The equation of a circle in standard form is
(x - h)² + (y - k)² = r²
where (h, k) are the coordinates of the centre and r is the radius
Here (h, k) = (4, 5) and r = 2 , thus
(x - 4)² + (y - 5)² = 2², that is
(x - 4)² + (y - 5)² = 4 ← equation of circle
Since triangle DEF = triangle JKL, m<D = m<J, m<E = m<K, m<F = m<L.
m<F = m<L = 90 degrees
m<K = m<E = 5(m<D)
but m<E + m<D = 90 degrees [right angled triangle]
5(m<D) + m<D = 90 degrees
6(m<D) = 90 degrees
m<D = 90 / 6 = 15 degrees.
Step-by-step explanation:
1. No: angles add to more than 180 deg.
2. Yes: each side's length is between the sum and difference of the lengths of the other two sides.
3. No: not every side's length is between the sum and difference of the lengths of the other two sides.
4. Yes: for example, place the 50 deg angle between the two given sides. Another side will then make the triangle.
5. Yes: for example, use 3 cm as the short leg in a 30-60-90 right triangle.
Answer:
- A) k = 18.75
- B) R(0.8) = 161419
- C) R(0.3) = 275
Step-by-step explanation:
<u>Given expression</u>
A) <u>Given</u>
<u>Solving for k</u>
- 10 = 6*e^(0.04k)
- e^(0.04k) = 10/6
- ln (e^0.04k) = ln (1.6666)
- 0.04k = 0.51
- k = 0.51/0.04
- k = 12.75
B) <u>Given</u>
<u>The value of R(0.8) is:</u>
- R(0.8) =
- 6*e^(0.8*12.75) =
- 6*e^(10.2) =
C) <u>Given</u>
<u>The value of R(0.3) is:</u>
- R(0.3) =
- 6*e^(0.3*12.75) =
- 6*e^(3.825) =
what upAnswer:
Step-by-step explanation: